1985
DOI: 10.1161/01.res.56.4.537
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the late fall in myocardial PCO2 and its relationship to myocardial pH after regional coronary occlusion in the dog.

Abstract: After acute regional coronary occlusion, myocardial tissue PCO2, as measured by mass spectrometry, rises, reaches a peak, and then gradually falls. This late fall in myocardial tissue PCO2 could be due to (1) a gradual increase in tissue blood flow (and hence improved carbon dioxide washout), (2) a gradual consumption of tissue bicarbonate, (3) a gradual reduction in the production of carbon dioxide due to progressive cellular damage, or (4) an artifact caused by the continued presence of the mass spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Mathemati cal modeling has demonstrated that following the first occlusion of this protocol, the increase in tissue PCO2 and [H+] far exceeds the levels predicted on the basis of decreased washout alone, indicating that an active production of COfe METABOLISM AND MYOCARDIAL STUNNING J CARD SURG 1993;8(Suppl):262-270 and [H +] occurs in response to the ischémie in sult. 5 In contrast, during the second occlusion in this model, the peak levels of myocardial PCO2 and [H +] do nor exceed the levels predicted on the basis of the decreased washout caused by the interruption of blood flow; i.e., there is no evidence of increased production of [H+] and CO2 during this occlusion. Hence, a metabolic correlate of postischemic cellular dysfunction is the inability of the myocardial cell to produce [H+] and CO2.…”
Section: Changes In Extracellular [H +] and Pco2mentioning
confidence: 51%
See 1 more Smart Citation
“…Mathemati cal modeling has demonstrated that following the first occlusion of this protocol, the increase in tissue PCO2 and [H+] far exceeds the levels predicted on the basis of decreased washout alone, indicating that an active production of COfe METABOLISM AND MYOCARDIAL STUNNING J CARD SURG 1993;8(Suppl):262-270 and [H +] occurs in response to the ischémie in sult. 5 In contrast, during the second occlusion in this model, the peak levels of myocardial PCO2 and [H +] do nor exceed the levels predicted on the basis of the decreased washout caused by the interruption of blood flow; i.e., there is no evidence of increased production of [H+] and CO2 during this occlusion. Hence, a metabolic correlate of postischemic cellular dysfunction is the inability of the myocardial cell to produce [H+] and CO2.…”
Section: Changes In Extracellular [H +] and Pco2mentioning
confidence: 51%
“…The late fall in both of these meta bolites is directly proportional to the magnitude of the ¡schemic insult and has been shown to be indicative of progressive cellular dysfunction. 5 When the occlusion is released at the end of 3 hours and reperfusion is allowed for 45 minutes, the increased washout restores the tissue PCO2 and [H+] to their preocclusion levels. During a second occlusion following this period of reper fusion, however, the rise in PCO2 and [H +] is sig nificantly lower than during the first occlusion.…”
Section: Changes In Extracellular [H +] and Pco2mentioning
confidence: 99%
“…Wikström et al determined a 300% increase in tissue lactate, and a 50% decrease in pyruvate after 15 minutes occlusion of a coronary artery (Wikström et al, 1995). Ischaemia-induced metabolic disturbances correlate well with ischaemia-induced myocardial acidosis (Ichihara and Abiko, 1982;Khuri et al, 1985). In a canine model, 50% reduction of left anterior descending coronary artery (LAD) flow caused a significant fall in myocardial pH within 15 minutes (Shortt et al, 1997).…”
Section: Myocardial Ischaemia and Cgrpmentioning
confidence: 99%
“…Furthermore, identical populations of C-fibres are activated in abdominal ischaemia with subsequent decrease in pH, and by lactic acid, but not by sodium lactate (Stahl and Longhurst, 1992). Ischaemia-induced metabolic disturbances correlate well with ischaemia-induced myocardial acidosis (Ichihara and Abiko, 1982;Khuri et al, 1985), and a reduction in extracellular pH to 5.5 has been demonstrated after acute coronary artery occlusion (Hirche et al, 1980). In preliminary studies in the pig models we have used, we recorded a pH value of 5.9 in the ischaemic zone after 35 min LAD occlusion.…”
Section: Release Of Cgrp By Low Phmentioning
confidence: 99%
“…O tampão bicarbonato (HCO 3 -/CO 2 ), presente no ambiente intra quanto extracelular com concentrações de 14,5 e 25 mM, respectivamente, ainda é pouco estudado em processos redox apesar de estudos demonstrarem que ele estimula reações de oxidação, peroxidação e nitração em biomoléculas (Hodgson e Fridovich, 1976;Berlett et al, 1990;Radi et al, 1993;Zhang, 2000;Bonini e Augusto, 2001;Liochev e Fridovich, 2002;Stadtman et al, 2005;Trindade et al, 2006;Ezraty et al, 2011;Queliconi et al, 2013) e que sua concentração é aumentada até 4 vezes durante a isquemia (Khuri et al, 1985). Existem diversos mecanismos conhecidos que levam à produção do radical bicarbonato ( Fig.…”
Section: -Tampão Bicarbonatounclassified